Comparison of Testosterone and Prostate-Specific Antigen Nadir Value between Castration Resistant Prostate Cancer and Non-Castration Resistant Prostate Cancer Patients after Androgen Deprivation Therapy - A Single Center Study in Indonesia - Safriadi, Ferry; Pramod, Sawkar Vijay; Partogu, Bernard; Wijayanti, Zola (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Prostate cancer is the second most commonly occurring cancer in adult males worldwide. Androgen deprivation therapy (ADT) is the mainstay treatment for patients with advanced prostate cancer. However, despite the low testosterone level (indicative of ADT success), most advanced prostate cancers progress into an androgen unresponsive or castrate resistant state; such cases are defined as castrate-resistant prostate cancer (CRPC) and were associated with worse outcomes and more rapid prostate cancer progression. This study aimed to compare the value of nadir testosterone level and nadir PSA in CRPC and non-CRPC patients who received ADT. AIM: This study was aimed to compare value of nadir testosterone level and nadir PSA in CRPC and non-CRPC patients who received ADT. METHODS: Prostate cancer patients receiving ADT in dr. Hasan Sadikin Bandung General Hospital in September 2018–September 2020 without previous history of CRPC and surgical castration, and prostate cancer with histopathological confirmation were included to the study. The patients prior had received complete blockade ADT with luteinizing hormone agonist (LHRH) goserelin acetate 10.8 mg injected subcutaneously per 3 months and oral anti-androgen bicalutamide 50 mg orally daily. Testosterone and PSA levels were assessed on 1st, 3rd, 6th, and 12th month. Patients then were grouped into CRPC group and non-CRPC group and further subdivided according testosterone levels (<20 and 20–500 ng/dL). Paired t-test and Chi-square test were used to analyze statistical difference (p < 0.05 deemed significant). RESULTS: Significantly higher baseline PSA (p = 0.002) and nadir PSA (p = 0.013) were found on the CRPC group. Nadir testosterone in CRPC group was higher than non-CRPC group but statistically insignificant (p = 0.849). Time to CRPC is faster in nadir testosterone 20–50 ng/dl group than in <20 ng/dl group but statistically insignificant (p = 0.837). CONCLUSION: Prostate cancer patients who had high baseline PSA and nadir PSA after ADT need a longer follow-up time and more frequent testing of the testosterone and PSA values. It can predict the incidence of CRPC and to ensure that prostate cancer patients receive adequate therapy.